Analisis Pengeluaran Rumah Tangga Miskin (Studi Kasus di Dusun Bulurejo Desa Kepek Kecamatan Saptosari Kabupaten Gunungkidul) - Suripto -; Aprillia Nurmala Paramita (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
This study aims to analyze the expenditure of poor households in Dusun Bulurejo. The data of this study were obtained from questionnaires (primary) and some observations and interviews directly with related parties, especially poor households on poverty level, heads of household income, number of family members, education level of head of household and total asset ownership (motor vehicle). The results of this study indicate that the household poverty rate of 81.1% is influenced jointly by the variables in the model, while the rest is influenced by other factors outside the model. Partially, income variable (X1) is significant and positively affect the level of household poverty in Bulurejo sub-village, the number of outgoing members (X2) is significant and positively affect the level of household poverty in Bulurejo sub-village, head of family education (X3) the level of household poverty in Bulurejo hamlet and ownership of assets (motor vehicle) (X4) is significant and positively affect the level of household poverty in Bulurejo hamlet.